2018
DOI: 10.1111/ans.14928
|View full text |Cite
|
Sign up to set email alerts
|

Surgical ultrasonography at the bedside: a comparison of surgical trainees with trained sonographers for symptomatic cholelithiasis – a first Australian experience

Abstract: Background: Symptomatic cholelithiasis accounts for a significant burden of emergency general surgical presentations in Australia and the Western population. Access to hepatobiliary ultrasonography to facilitate diagnosis can lead to delays in timely treatment. Surgical ultrasonography at the bedside (SUB) can mitigate this barrier to patient care. This study assessed the diagnostic accuracy of SUB by trainees versus formal ultrasonographer or computed tomography examination for suspected symptomatic cholelith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…This compares favourably with the 2017-2018 Australian study of surgical trainees, which recorded a kappa of 0.62 (95% CI 0.46-0.77) for the finding of gallstones. 7 These results are similar to other previously published studies. Two studies of bedside ultrasound performed by emergency medicine physicians have reported sensitivities of 88% and 87% and specificities of 90% and 88% for the finding of gallstones.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This compares favourably with the 2017-2018 Australian study of surgical trainees, which recorded a kappa of 0.62 (95% CI 0.46-0.77) for the finding of gallstones. 7 These results are similar to other previously published studies. Two studies of bedside ultrasound performed by emergency medicine physicians have reported sensitivities of 88% and 87% and specificities of 90% and 88% for the finding of gallstones.…”
Section: Discussionsupporting
confidence: 93%
“…We were unable to replicate the results 2017-2018 Australian study of surgical trainees, which recorded a sensitivity and specificity of 94.9% and 100%, respectively. 7 However, other published studies of bedside ultrasound for acute cholecystitis have generally reported much lower sensitivities and specificities. For example, studies of bedside ultrasound performed by surgeons in Sweden, Japan and Iran have reported sensitivities of 60%, 84.2% and 89.6% and specificities of 98.6%, 92.1% and 96.6%, respectively, for the imaging diagnosis of acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptable rates of diagnostic accuracy for bedside ultrasound performed by surgeons, in comparison to formal departmental ultrasound scans, have been demonstrated . Some published studies have reported sensitivities and specificities of well over 90% for the detection of gallstones alone . Ultimately, it is a realistic prospect for bedside ultrasound performed by surgical staff to become a standard diagnostic tool for the confirmation of acute cholecystitis or acute gallstone disease, followed directly by surgical treatment in the form of cholecystectomy.…”
mentioning
confidence: 99%
“…In this issue of ANZ Journal of Surgery , Gaszynski et al report encouraging diagnostic results for bedside gallbladder ultrasound scans performed by surgical trainees at Campbelltown and Liverpool Hospitals in Sydney in the first documented experience in Australia and New Zealand. This is a prospective study of diagnostic accuracy for bedside ultrasound of the gallbladder performed by surgical trainees following a single short instruction session compared to formal departmental biliary ultrasound performed by an accredited ultrasonographer.…”
mentioning
confidence: 99%